Preliminary analysis of Ku-Band rain fade data for earth-to-satellite path measured in Malaysia - Hassan, Dao; Islam, Md. Rafiqul; Al-Khateeb, Khalid A. Saeed; Khan, Sheroz (2011)
The dynamic characteristics of rain fade slope are one of the important factors in the determination of the earth-to-space communication system availability. It is also useful in the design of the fade countermeasures. This paper investigates the rain fade slope which is one of the main features of fade dynamics with 0.1s, 0.5s, 1s, 2s, 5s and 10s sampling time intervals. The rain fade slope model proposed by the ITU-R was compared with the corresponding statistics obtained from rain attenuation data measured using MEASAT3 downlink at Ku-band in Malaysia during May 2010 – June 2011. Significant discrepancies have been observed between the measured fade slope data and that predicted by the ITU-R prediction model with different sampling time interval.